2015
DOI: 10.1121/1.4932028
|View full text |Cite
|
Sign up to set email alerts
|

The influence of hearing-aid compression on forward-masked thresholds for adults with hearing loss

Abstract: This paper describes forward-masked thresholds for adults with hearing loss. Previous research has demonstrated that the loss of cochlear compression contributes to deficits in this measure of temporal resolution. Cochlear compression can be mimicked with fast-acting compression where the normal dynamic range is mapped to the impaired dynamic range. To test the hypothesis that fastacting compression will most-closely approximate the normal ability to perceive forward-masked pure-tones, forward-masked threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The predicted increase in the DoFM of the aided HI is most likely due to the overall gain introduced by both amplification schemes, which increased the audibility of the stimulus. This is in line with the findings of Brennan [6], who found an improvement in forward-masking thresholds even with slow-acting compression. The advantage of fast-acting compression with a very short release time, such as the one used in the present study, is that the gain changes quickly enough to improve the output SNR.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The predicted increase in the DoFM of the aided HI is most likely due to the overall gain introduced by both amplification schemes, which increased the audibility of the stimulus. This is in line with the findings of Brennan [6], who found an improvement in forward-masking thresholds even with slow-acting compression. The advantage of fast-acting compression with a very short release time, such as the one used in the present study, is that the gain changes quickly enough to improve the output SNR.…”
Section: Discussionsupporting
confidence: 92%
“…The speed of gain reduction and recovery in a compressor are governed, respectively, by its attack and release time constants. Attack times ranging from 1 to 10 ms have been reported [6,7]. Such short attack times allow the hearing aid to quickly react to sudden increases in the signal level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that multiband DRC with compression attack and release time-constants of 10 ms can restore normal loudness perception for listeners with sensorineural hearing loss (LSNHL; Strelcyk et al 2012). It has also been demonstrated that measures of auditory temporal resolution that are assumed to be affected by recruitment, such as gap detection and forward masking, can at least partly be restored for LSNHL by fast-acting DRC with attack and release times less than 60 ms (e.g., Brennan et al 2015;Kowalewski et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Most of us meet in person at the annual meeting of the ARO (as well as other professional conferences), where our network has secured equal access to podium and poster sessions through sign language interpreters, hearing-assistive technology, and real-time captioning. The efficacy of our distributed model of peer support, mentorship, and integration with the wider scientific community is validated in part by those members of HI-ARO who have become academic faculty (4-6), secured competitively funded national research awards, and published influential manuscripts in high-impact journals [e.g., (7-10]. …”
mentioning
confidence: 99%